Register Now

222-9+11+12:2*14+14 = ? ( )

## Toán Lớp 8: $\frac{x+3}{x-3}$- $\frac{x-3}{x+3}$+ $\frac{x^2-9x}{x^2-9}$

Toán Lớp 8: $\frac{x+3}{x-3}$- $\frac{x-3}{x+3}$+ $\frac{x^2-9x}{x^2-9}$

## Comments ( 2 )

1. Giải đáp:
= {x}/{x – 3}
Lời giải và giải thích chi tiết:
{x + 3}/{x – 3} – {x – 3}/{x + 3} + {x^2 – 9x}/{x^2 – 9}
= {x + 3}/{x – 3} – {x – 3}/{x + 3} + {x^2 – 9x}/{x^2 – 3^2}
= {x + 3}/{x – 3} – {x – 3}/{x + 3} + {x^2 – 9x}/{(x – 3)(x + 3)}
= {(x + 3)(x + 3)}/{(x – 3)(x + 3)} – {(x – 3)(x – 3)}/{(x – 3)(x + 3)} + {x^2 – 9x}/{(x – 3)(x + 3)}
= {x^2 + 6x + 9}/{(x – 3)(x + 3)} – {x^2 – 6x + 9}/{(x – 3)(x + 3)} + {x^2 – 9x}/{(x – 3)(x + 3)}
= {x^2 + 6x + 9 – (x^2 – 6x + 9) + x^2 – 9x}/{(x – 3)(x + 3)}
= {x^2 + 6x + 9 – x^2 + 6x – 9 + x^2 – 9x}/{(x – 3)(x + 3)}
= {(x^2 – x^2 + x^2) + (6x + 6x – 9x) + (9 – 9)}/{(x – 3)(x + 3)}
= {x^2 + 3x}/{(x – 3)(x + 3)}
= {x(x + 3)}/{(x – 3)(x + 3)}
= {x.1}/{(x – 3).1}
= {x}/{x – 3}
#SunHee

2. Giải đáp + Lời giải và giải thích chi tiết:
(x+3)/(x-3)-(x-3)/(x+3)+(x^2-9x)/(x^2-9)
=((x+3)(x+3))/((x-3)(x+3))-((x-3)(x-3))/((x+3)(x-3))+(x^2-9x)/(x^2-9)
=((x+3)^2)/((x-3)(x+3))-((x-3)^2)/((x+3)(x-3))+(x^2-9x)/(x^2-9)
=(x^2+6x+9-x^2+6x-9+x^2-9x)/(x^2-9)
=(x^2+3x)/(x^2-9)
=(x(x+3))/((x-3)(x+3))
=x/(x-3)